Evolution of Higher Education Research in Developing Countries: A Scopus-Based Bibliometric Study - Musleh; Benny Prasetiya; Febry Suprapto; Khoiriyah (PT. Caesarindo Triloka Persada, 2026)
In the past two decades, higher education research in developing countries has experienced significant growth, driven by globalization, digitalization, and educational transformation. However, the scientific contribution of developing countries remains relatively low compared to developed nations. This study aims to analyze the evolution, trends, and collaboration patterns of higher education research in developing countries using a Scopus-based bibliometric approach. Following the PRISMA 2020 protocol, data were collected from 2000–2025 and analyzed using VOSviewer and Bibliometrix to identify publication trends, thematic structures, and author networks. The results reveal a substantial increase in publication productivity after 2015, reflecting stronger international collaboration and growing interest in issues such as institutional change, digital transformation, and socio-economic development. Social sciences and health-related disciplines dominate, while emerging research areas such as digitalization, knowledge management, and sustainability are gaining attention. The novelty of this research lies in the development of a socio-technical–institutional model that integrates technological innovation, organizational transformation, and human capital development as key drivers of sustainable academic progress. This study contributes theoretically by mapping the evolution of research themes and empirically by offering insights into the collaboration networks that shape global higher education research. Practically, it provides policymakers and institutions with a data-driven understanding to strengthen research capacity, promote equity, and enhance the visibility of developing countries in the global academic ecosystem.